Rancang Bangun Sistem Monitoring Kerja Praktik Mahasiswa Teknik Informatika Berbasis Cloud Computing - Hendrawan, Nalis; Udaya Manarfa, Wa Ode Rahma Agus; La Atina, La Atina; Hidayat, Farhan (Informatics Engineering Department, Dayanu Ikhsanuddin University, 2025)
The monitoring process of students’ internship (practical work) activities often faces various challenges, particularly related to time efficiency, limited access to information, and suboptimal coordination among students, academic supervisors, and internship coordinators. These conditions result in ineffective monitoring, evaluation, and documentation of internship activities. This study aims to design and develop an integrated and centralized internship monitoring system for Informatics Engineering students that can be accessed online anytime and anywhere. The system development method employed is the waterfall model, which consists of requirements analysis, system design, implementation, and testing stages. The system is developed based on cloud computing technology to support service availability, system scalability, and efficient data management. The results of this study indicate that the developed system is a web-based application that enables students to upload internship progress reports periodically, allows supervisors to provide feedback and evaluations in real time, and assists internship coordinators in monitoring all internship activities comprehensively. The implementation of this system has been proven to improve the efficiency of the monitoring process, enhance communication flow among related stakeholders, and facilitate more systematic and structured documentation and assessment of students’ internship performance.